The Challenges of Copyright Protection in the Digital Age: Between Innovation and Piracy - Asfrianda Mulia Nasution; Akbar Rayfades; Mu’ammar Rafsanjany; Awal Diwangga (ISNU Nine-Star Multidisciplinary Journal, 2026)
The development of digital technology has brought significant changes in the pattern of creation, distribution, and consumption of copyrights. On the one hand, the digital era encourages innovation and ease of access to intellectual works, but on the other hand it also increases the practice of copyright infringement such as digital piracy. This condition poses a serious challenge to the copyright law protection system, especially in maintaining a balance between the protection of the interests of creators and the public interest. This research aims to analyze the challenges of copyright protection in the digital era and examine legal remedies that can be taken in dealing with piracy practices. The research method used is normative juridical research with a legislative approach and a conceptual approach, through the study of laws and regulations related to copyright and relevant legal literature. The research stages include the collection of primary and secondary legal materials, normative analysis, and deductive conclusions. The results of the study show that weak law enforcement, low public legal awareness, and faster technological developments than regulations are the main factors for the rise of digital piracy. Therefore, it is necessary to strengthen regulations, increase public legal literacy, and synergy between the government, creative industry players, and digital platforms to create an effective and fair copyright protection system in the digital era.